POPULATION PROJECTION ANALYSIS IN MLANDINGAN DISTRICT - Sofi Chorina Ramadhani; Sri Astutik; Fahrudi Ahwan Ikhsan; Era Iswara Pangastuti (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2020)
This research aims toanalyze the Population Projection of Mlandingan Sub-district in 2020. The focus of this study is the Birth, Death, and Population Migration Data that occurred in Mlandingan District which is then projected into a map. The research method used in this study is a quantitative qualitative method. Sources of data were obtained through the Regional Statistics Center Bada Data, books, journals, and web pages related to the topic of discussion, namely the 2020 Mlandingan District Population Projection. The data collection technique used was a literature study, namely reading data from the regional statistical center agency, journals. previous journals, books, and related web pages as well as component methods in determining population projections. While the data analysis technique used qualitative analysis. The results showed that the population projection of MlandinganSubdistrict was divided into 3 types, namely Low Population Projection for villages in mountainous areas, Medium for villages in the middle of the sub-district, and High for coastal villages. Based on this research, the government should be able to determine the appropriate regional development planning in accordance with the population projection data that has been obtained.